Effects of flywheel vs. traditional resistance training on neuromuscular performance of elite ice hockey players - Puustinen, J.; Venojärvi, M.; Haverinen, M.; Lundberg, T. R. (The Journal of Strength and Conditioning Research, 2023)
This study aimed to examine the effects of 8 weeks of flywheel (FW) vs. traditional resistance training on neuromuscular performance of elite ice hockey players during the off-season. Eighteen male players (U-18 to U-21) were assigned to a flywheel group (FG) or traditional training group (TG). The FG (n = 9) performed FW training with 4 different exercises (3-4 sets × 6-7 repetitions). The TG (n = 9) used barbells and free weights (4 sets × 4-12 repetitions). Outcome measures included loaded and unloaded countermovement jumps (CMJs) and a 200 m sprint test that included split times and direction changes. There were no group effects (analysis of covariance with adjustments for pretest values, all p > 0.05, all effect sizes <0.8), suggesting comparable performance improvements between groups. Within-group changes for the unloaded CMJ were 5.7% in FG vs. 4.8% in TG. Similar or slightly greater improvements were seen for the loaded CMJs. For sprint times, there were improvements in both groups for the split time of the first 20 m (FG: -3.2 vs. TG: -2.6%) and also for the 200 m total sprint time (FG -1.8% and TG -1.5%). In conclusion, although FW resistance training improves neuromuscular performance in elite ice hockey players, it does not elicit superior improvements compared with traditional resistance training in players with no prior experience with this training method.